On Weakly Semi-$\mathcal{I}$-Open Sets - Devi, V. Renuka; Sivaraj, D. (Sarajevo Journal of Mathematics, 2024)
A decomposition of continuity via ideals is given. Characterizations of completely codense ideals are given in terms of weakly semi-$\mathcal{I}$-open sets. Also, properties of weakly semi-$\mathcal{I}$-open sets and their relation with other sets are discussed. 2000 Mathematics Subject Classification. 54A05, 54A10